Prevalence and Risk Factors of ESBL-producing Enterobacteriaceae in The Community - Nia Krisniawati; Anriani Puspita Karunia Ning Widhi (Journal of Biomedicine and Translational Research, 2021)
Background: World Health Organization (WHO) data collection of Escherichia coli resistant to cephalosporin generation III already confirmed in 86 countries. Incredibly high carrier prevalence rates were also widely developed in Thailand, Egypt, and China. The Faculty of Medicine's research team at Jenderal Soedirman University, Purwokerto,  discovered at the beginning of 2018 that Extended Spectrum β-Lactamase (ESBL) E. coli carriers throughout the 2015 class students were 26.8 percent.Objective: This research investigated the Prevalence and associated factors of ESBL-producing Enterobacteriaceae (EPE) asymptomatic carriers in the community.Methods: The participant fill a questionnaire, and samples were taken from rectal swabs using Amies transport medium (Labware Charuzu), and then models were analyze using HiCrome ™ ESBL Agar Base (Himedia, India). Analysis of its Prevalence and Resistance Predictors uses IBM SPSS Statistics Version 22.0 for Windows (Armonk, NY: IBM Corp).Results: The Prevalence of EPE asymptomatic carriers in the community in Purwokerto was 66.7%. In the bivariate analysis, subjects who took antacids in the last eight weeks, history of hospitalization in the previous 12 months, the habit of consuming milk, yogurt, cheese, meat, seafood, and raw vegetables did not show any significant difference. Frequent chicken and freshwater fish consumption tended to be a risk factor for ESBL-producing Enterobacteriaceae with PR 1.462, 95% CI (1.115-1.918); PR 1.666, 95% CI  (0.936-2.966); however, in the multivariate logistic regression analysis, this was not significant.Conclusion: The Prevalence of EPE asymptomatic carriers in the community in Purwokerto is 66.7%. All variables did not become any significant of ESBL-producing Enterobacteriaceae. However, ESBL remains an emerging antimicrobial resistance.